Application of a material model based on the Johnson-Cook and Gurson-Tvergaard-Needleman model in ship collision and grounding simulations. (1st June 2020) - Wang, Zeping; Hu, Zhiqiang; Liu, Kun; Chen, Gang
Abstract: Nonlinear numerical simulation has become an important tool for analysing dynamic responses and energy dissipation of structures during ship collision and grounding scenarios. However, determining a globally acknowledged failure criterion remains a challenging task. In this paper, a material model based on the Johnson-Cook model and the Gurson-Tvergaard-Needleman (GTN) model is proposed. The GTN model assumes that the fracture of materials is caused by void growth and coalescence, but it is only applicable to a relatively high value of the stress triaxiality and significantly overestimates the carrying capacity of materials under a shear loading condition. Moreover, the GTN model is suitable for the relatively low strain rates, while at higher strain rates, such as structural impact problems, the numerical simulation results are not accurate, so the material model proposed in this paper solves this problem by including the strain rate effect and combining the void nucleation and coalescence. Furthermore, in order to verify the accuracy of the proposed model's application in the LS-DYNA programme, a set of model tests were conducted. A quasi-static tensile test, high-speed tensile test and falling weight impact test were performed. By comparing the numerical simulation results with those of the experiment results, it is determined that the proposed material model can describe the structural damage extremely well, which demonstrates the proposed model's applicability for structural failure response prediction in ship collision and grounding simulations. Highlights: A material model is proposed to describe the ductile fracture behaviour of steel material. Quasi-static and high-speed tensile tests are performed to obtain the properties of the material. Falling weight impact tests are performed on the stiffened plate struck by an indenter. The finite element simulation results show good agreement with experimental results. The proposed material model is applicable for structural failure response prediction in ship collision simulations.